VLF Wave generation by the erenkov process in the inner magnetosphere [3] - Singh R.P.; Singh R.N. (My University, 2025)
ELECTROMAGNETIC waves of very low frequencies (VLF) are generated by a variety of natural processes. This letter is to offer support for the erenkov process, in which radiation is produced by the interaction of moving electrons with the ambient plasma. © 1970 Nature Publishing Group.